Antitumor properties of an anti-idiotypic monoclonal antibody in relation to N-glycolyl-containing gangliosides - Vázquez, Ana María (2000)
We examined the antitumor effects of 1E10 monoclonal antibody, an anti-idiotypic IgG to an IgM monoclonal antibody, named P3, that reacts specifically with N-glycolyl-containing gangliosides and also recognizes antigens in human breast and melanoma tumors. Two murine tumor cell lines positive for the P3 antibody, F3II mammary carcinoma (BALB/c) and B16 melanoma (C57BL/6), were employed. In BALB/c mice, vaccination with several i.p. doses at 14-day intervals of 50 microgram of 1E10 coupled to keyhole limpet hemocyanin in Freund's adjuvant, significantly reduced s.c. tumor growth of F3II carcinoma cells and the number of spontaneous lung metastases. Also, the effect of 1E10 as a biological response modifier on tumor lung colonization was evaluated in C57BL/6 mice injected i.v. with B16 melanoma cells. Interestingly, i.v. administration of 10 microgram of uncoupled 1E10 antibody, 10-14 days after inoculation of B16 cells, dramatically reduced the number of experimental metastases in comparison with lungs from mice treated with an irrelevant IgG. The present data suggest that this 'non-internal image' anti-idiotypic monoclonal antibody may activate more than one mechanism of antitumor response against melanoma and mammary tumor cells.